Colleagues and Competitors: How Internal Social Comparisons Shape Organizational Search and Adaptation. (June 2019) - Baumann, Oliver; Eggers, J. P.; Stieglitz, Nils
Intra-organizational comparisons—managers and units benchmarking their performance against each other—can turn colleagues into competitors. To better understand when organizations should allow or even encourage internal social comparisons, we study their implications for organizational adaptation and performance. We conceptualize internal social comparisons as an upstream competitive process that shapes performance aspirations and creates interdependencies in search behavior. We distinguish this from downstream, product market competition or complementarities where performance is interdependent across units. Integrating both aspects into a computational model, we show how internal social comparisons affect adaptation and performance through two mechanisms: a balancing effect whereby the organization is guaranteed to contain both exploring and exploiting units, and a stabilizing effect whereby internal social comparisons protect against abandoning existing technologies too early. The benefits of upstream comparisons are accentuated when units are downstream complements, helping synchronize search. When units are downstream competitors, these benefits disappear, suggesting substitutive effects. We highlight empirical implications and discuss theoretical links to work on intra-organizational competition, social comparisons and aspiration-driven search, diversification and performance, and the adaptation of multi-business firms.